Antileishmanial activity and cytotoxicity of ent-beyerene diterpenoids - Murillo, Jilmar A.; Gil, Juan F.; Upegui, Yulieth A.; Restrepo, Adriana M.; Robledo, Sara M.; Quinones, Winston; Echeverri, Fernando; San Martin Barrientos, Aurelio Del Carmen; Olivo, Horacio F.; Escobar, Gustavo (My University, 2019)
We describe the in vitro activity of two natural isomeric ent-beyerene diterpenes, several derivatives and synthetic intermediates. Beyerenols 1 and 2 showed EC50 of 4.6 +/- 9.4 and 5.3 +/- 9.4 mu g/mL against amastigotes of L. (V) brazilensis, with SI of 5.1 and 7.7, respectively. Beyerenol 1 was synthesized from stevioside. In vivo experiments with bereyenols showed cure in 50% of hamsters infected with L. (V) brazilensis topically applied as Cream I (beyerenol 1, 0.81%, w/w) and Cream III (beyerenol 2, 1.96%, w/w). These results suggest that beyerenols are potential candidates for cutaneous leishmaniasis chemotherapy by topical application. In vitro assays of amastigotes of L. (V) brazilensis showed EC50 of 1.1 +/- 0.1 and 1.3 +/- 0.04 mu g/mL, with SI of 3.1 and 3.5 for hydrazone intermediates 10 and 11, respectively.
Keywords: ent-beyerene diterpenoids; leishmania brazilensis; antileishmanial; semisynthesis; steviol